La Sanción Penal a las Personas Jurídicas establecida en el Código Orgánico Integral Penal atenta contra la Naturaleza del Derecho Societario - Ximena Lucia, Carrasco Ruiz (2016)
On August 10, 2014, with the force of the Code Integral Penal a new legal instrument in Ecuadorian criminal matters, immersed changes in this law does not cover only aggravate the penalties or create new offenses is generated, but causes structural changes qualifying the legal person as a subject of criminal law. This theory is studied in order to know, why started criminal liability of legal persons established, the historical background, the kind of crimes that can be committed, how are typified these behaviors; and penalties attached to them. These questions are analyzed against standards and criminal principles such as: theory of crime, individualization of sentences and the end of it, rules in civil matters qualifying legal person as a fictitious entity and incapable relative, rules and guarantees that the companies Act provides partners or shareholders when they have not participated in the crime, administrative rules provide for penalties for companies that violate public order; and against the doctrine of shifting the corporate veil, which allows without the protection of shareholders and shareholders to punish offenders who took advantage of this protection to commit the crime and in the same way, protect the rights of partners They did not participate in the commission thereof